Corneal Manifestations of Systemic Sclerosis. (18th August 2019) - Nagy, Annamaria; Rentka, Aniko; Nemeth, Gabor; Ziad, Hassan; Szücs, Gabriella; Szekanecz, Zoltán; Gesztelyi, Rudolf; Zsuga, Judit; Aszalos, Zsuzsa; Szodoray, Peter; Kemeny-Beke, Adam
ABSTRACT: Purpose : Corneal involvement in systemic sclerosis (SSc) is rare, but due to rich collagen composition cornea is especially vulnerable to connective tissue diseases. Therefore, our aim was to evaluate corneal parameters of SSc patients. Methods : The study included 32 SSc patients and 39 control subjects with no ocular symptoms or ocular surface disorders. All study participants underwent Pentacam evaluation and objective signs of dry eye disease (DED), and clinical parameters were evaluated. Results : All pachymetric values, most of the corneal front surface, corneal volume, as well as anterior chamber depth measurements were significantly lower in the SSc group than in the control group ( p  < 0.05). Significant negative correlation was found between corneal parameters and age on the one hand, and disease duration on the other. Conclusions : Early recognition of corneal impairment, a possible extraintestinal manifestation of SSc, should be included in the check-up of the disease in order to reduce sight-threatening complications.